Responses of capsicum frutescenes cultivar serrano and capsicum annuum cultivar capistrano to meloidogyne incognita race 2,salinity and growth period - Aluvilu, Anastasia N. (University of Limpopo (Turfloop Campus), 2010)
Refer to document
Thesis (M.A. (Horticulture)) --University of Limpopo, 2010
Keywords: Capsicum frutescenes cultivar serrano; Capsicum annuum cultivar capistrano; Meloidogyne incognita race 2; Soil salinity; 631.416; Soil salinization; Peppers; Soil nematodes; Soil, salts in -- South Africa